2016
DOI: 10.1016/j.socscimed.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

First depressed, then discriminated against?

Abstract: Each year a substantial share of the European population suffers from major depression. This mental illness may affect individuals' later life outcomes indirectly by the stigma it inflicts. The present study assesses hiring discrimination based on disclosed depression.To this end, between May 2015 and July 2015, we sent out 288 trios of job applications from fictitious candidates to real vacancies in Belgium. Within each trio, one candidate claimed to have become unemployed only recently, whereas the other two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
0
32
3
1
Order By: Relevance
“…In line with this, the relationship between employment and mental health has received growing attention in the literature ( Baert et al, 2016 , Greve and Nielsen, 2013 , Paul and Moser, 2009 , Tefft, 2012 ). Previous studies indicate that they appear to influence each other.…”
Section: Introductionmentioning
confidence: 93%
“…In line with this, the relationship between employment and mental health has received growing attention in the literature ( Baert et al, 2016 , Greve and Nielsen, 2013 , Paul and Moser, 2009 , Tefft, 2012 ). Previous studies indicate that they appear to influence each other.…”
Section: Introductionmentioning
confidence: 93%
“…Depression remains a stigmatized identity (Peluso & Blay, 2009; Wood et al., 2014), particularly in the workplace where stereotypes of individuals with depression as lazy, incompetent, emotional, or crazy (Follmer & Jones, 2017) conflict with the image of the ideal worker who is fully committed to and productive in their work role (Reid, 2011). The stigmatization of depression can also lead to negative workplace outcomes for those diagnosed with this disorder including discrimination (Baert et al., 2016). Indeed, prior work has demonstrated that managers have concerns about hiring individuals with mental illness, such as depression (Hand & Tryssenaar, 2006).…”
Section: Study 1: Identifying Motives For the Disclosure Of Depression Among Workersmentioning
confidence: 99%
“…Correspondence studies are best suited to measure the effect of an individual characteristic on the chances of getting a job (Baert et al , 2016; Riach and Rich, 2002; Neumark, 2012, 2016). It consists in building fictitious applications that are practically identical apart from the trait whose effect we want to evaluate, and then to send them simultaneously in response to the same job offers.…”
Section: Methodsmentioning
confidence: 99%